Proceedings of the 2005 ACM Symposium on Software Visualization 2005
DOI: 10.1145/1056018.1056027
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing multiple evolution metrics

Abstract: Observing the evolution of very large software systems needs the analysis of large complex data models and visualization of condensed views on the system. For visualization software metrics have been used to compute such condensed views. However, current techniques concentrate on visualizing data of one particular release providing only insufficient support for visualizing data of several releases.In this paper we present the RelVis visualization approach that concentrates on providing integrated condensed gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 20 publications
0
57
0
1
Order By: Relevance
“…These tools essentially offer a timeline for the visualization of software artifacts, such as project hierarchies [15] or metric values [16].…”
Section: Existing Toolsmentioning
confidence: 99%
“…These tools essentially offer a timeline for the visualization of software artifacts, such as project hierarchies [15] or metric values [16].…”
Section: Existing Toolsmentioning
confidence: 99%
“…A number of approaches give summarized information on package relationships and their evolution: the Butterfly by Ducasse et al gives a high-level client/provider trend of package dependencies [DLP05]; Pzinger et al show the evolution of package metrics using Kiviat diagrams [PGFL05]; Chuah and Eick use rich glyphs to characterize software artifacts and their evolution (number of bugs, number of deleted lines, kind of language...) [CE98]. In particular, the timewheel exploits preattentive processing, and the infobug presents many different data sources in a compact way; finally, D'Ambros et al reveal package coupling by showing evolutions that are correlated in time [DL06].…”
Section: Related Workmentioning
confidence: 99%
“…The authors applied the visualization to analyze historical relationships among modules of a large telecommunications system and showed that it supported the understanding of the system architecture. Pinzger et al [47] proposed a visualization technique based on Kiviat diagrams. The visualization provides integrated views on source code metrics in different releases of a software system together with coupling information computed from CVS log files.…”
Section: Design-level Visualizationmentioning
confidence: 99%